The Porous Border on Nigeria Economics and Security Implications - Samuel Olanrewaju Oladopo; David Toyin Aladejebi; Anthonia Opeyemi Ayeni (RIRAI Publisher, 2021)
Nigeria borders have been said to have been too porous to have been allowing for the influx of arms and ammunitions as well as illegal and adulterated goods coming into the country without control. Relevant literatures were reviewed in other to come up with the writers’ opinion on the topic. It was discovered that the porous borders have been affecting the security of the country, also, the porous border affects the country economically as illegal entry of goods denied country from collecting taxes while citizens are facing problems of buying adulterated goods. It therefore, recommend that: agencies responsible for policing our boarders be alive to their responsibility, they should always shun corruptions.